LEARNING OBSTACLES MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA PADA MATA KULIAH KALKULUS - Muh Rizal; Nurhayadi; Rifka (STKIP Andi Matappa, 2024)
Research with the aim of uncovering students' learning obstacles in calculus courses by applying the case method. To achieve this goal, learning obstacles were explored in calculus material after being taught by applying the case method. These learning obstacles were explored through Brousseau's (2002) categories using observation, think aloud and in depth interviewing methods. The results obtained were that students in the Mathematics Education Study Program generally experienced epistemological obstacles in the calculus course, especially in the material on inequalities and operations on functions. Students have a very limited concept of the problem, so that when faced with a problem with a different editorial team, it is difficult for them to solve it. Apart from that, students also experience ontogenic obstacles in this material, they are not able to understand because the level of material being studied is too high, it is not connected to the knowledge they already have, students also experience didactical obstacles because the learning process during the Covid-19 pandemic is based online while the model This learning is not yet familiar to them.